Strategies for fuel property enhancement for second-generation multi-feedstock biodiesel - Goh B.H.H.; Chong C.T.; Ong H.C.; Milano J.; Shamsuddin A.H.; Lee X.J.; Ng J.-H. (Elsevier Ltd, 2023)
Antioxidants; Blending; Catalysis; Catalysts; Diesel engines; Esters; Fatty acids; Feedstocks; Molar ratio; Physicochemical properties; Potassium hydroxide; Sustainable development; Transesterification; Acid value; Alternative energy; Biodiesel blending; Biodiesel production; Environmental sustainability; Fuel properties; Jatropha oil; Lower acids; Molar ratio; Waste cooking oil; Biodiesel